KARAKTERISASI FITOPLASMA PENYEBAB PENYAKIT LAYU KELAPA DI PULAU DERAWAN MENGGUNAKAN RFLP IN SILICO - Prasetyo, Agus Eko; Mutaqin, Kikin Hamzah; ., Giyanto (Universitas Lampung, 2017)
Characterization of phytoplasmas associated with coconut wilt disease in Derawan Island using in silico RFLP. Coconutwilt disease has been reported in Derawan Island that resulted in eradication up to 10% of the total cultivated palms. Theobjective of this study was to detect and characterize phytoplasmas associated with coconut wilt disease in Derawan islandusing nested PCR technique and in silico RFLP based on 16S rRNA gene sequences. Detection of phytoplasmas was performedusing nested PCR method, cloning of nPCR products, sequencing, and analysis of sequencing results using in silico RFLP.The results revealed that phytoplasmas could not be detected by PCR using P1/P7 primer pairs however it could be amplifiedby nested PCR using R16F2n/R16R2 primer pairs resulting amplicon at about 1.25 kb. In silico RFLP analysis indicated thatphytoplasmas associated with coconut wilt disease in Derawan Island belong to 16SrII (witches broom phytoplasma). PCRproduct of the nPCR need to be sequenced because the R16F2n/R16R2 primer will also amplify the other bacterial species, mainly from Gram positive bacteria.